Prática reflexivo narrativa para promoção de qualidade de vida em cuidadoras - Ura, Carmen dos Santos Godoy [UNESP] (Universidade Estadual Paulista (UNESP), 2025)
Affects and routines are impacted by caregiving activity, which primarily takes place within the family microsystem and is predominantly carried out by women. Care is considered fundamental as support for development throughout life. The strengthening of individuals and their bonds is the objective of narrative practices, through the construction of new narratives about themselves, considering the contexts in which self-knowledge and self-efficacy are favored by interaction. Among the possible actions with narrative practices, self-knowledge and the alignment of choices with desires, needs, and values ​​are facilitated by the intervention method in Career Guidance. Considering this theme, the objective of this dissertation is investigate the outcome of the intervention through Career Guidance based on narrative practices with informal caregivers, in order to evaluate and promote the quality of life of this population. Four caregivers were the subjects of the research, and the guidance took place in 10 reflective-narrative meetings and an initial interview. The Assessment of Family Needs (AFN) and Family Quality of Life Scale (FQoL) instruments were applied to assess the baseline of the caregivers in relation to their perception of family quality of life. The sessions were recorded, transcribed, and interpreted using content analysis. The results, corroborating what is found in the literature, indicate that overload, guilt, and fear regarding the quality of care are felt by the caregivers. The creation and strengthening of bonds and the opening and planning of new forms of interaction with the cared-for individuals and support network were made possible by the opportunity to narrate the experiences of care and interaction in their micro, meso, and macro systems. The health and well-being of caregivers are considered significant for the development of those being cared for; therefore, the opening of possibilities for their particular subjectivation, which will influence the quality of the bond with the cared-for person, is provided by offering a listening ear to the narratives of these women. It is argued, therefore, that practices like this are considered necessary and relevant, and that they need funding so that they can be taken to other spaces, such as the health and assistance network for people receiving care.

A atividade de cuidar impacta afetos e rotinas, acontece principalmente no microssistema familiar e é majoritariamente exercida por mulheres. O cuidado é fundamental como suporte ao desenvolvimento ao longo da vida. As práticas narrativas objetivam o fortalecimento das pessoas e de seus vínculos, por meio da construção de novas narrativas sobre si, considerando os contexto nos quais a interação favorece o autoconhecimento e a autoeficácia. Dentre as ações possíveis com práticas narrativas, o modo de intervenção em OP facilita o autoconhecimento e o alinhamento de escolhas com desejos, necessidades e valores. Considerando essa temática, o objetivo desta dissertação é investigar a resultante da intervenção por meio de OP fundamentada em práticas narrativas com cuidadoras informais, a fim de avaliar e promover qualidade de vida a essa população. Os sujeitos da pesquisa foram 4 cuidadoras, as orientações aconteceram em 10 encontros reflexivo narrativos e uma entrevista inicial. Aplicaram-se os instrumentos ANF e QdVF Brasil para aferência da linha de base das cuidadoras em relação à percepção de qualidade de vida familiar. As sessões foram gravadas, transcritas e interpretadas a partir da análise de conteúdo. Os resultados corroboram com o que consta na literatura, indicando que cuidadoras sentem sobrecarga, culpa e medo em relação à qualidade do cuidado. A possibilidade de narrar as experiências de cuidado e de interação em seus micro, meso e macro sistemas possibilitou a criação e fortalecimento de vínculos e abertura e planejamento de novas formas de interação com as pessoas cuidadas e rede de apoio. A saúde e bem estar das cuidadoras são significativos para o desenvolvimento de quem é cuidado, desta forma, oferecer uma escuta para as narrativas dessas mulheres é abrir possibilidades para a subjetivação particular delas, que influenciará a qualidade do vínculo com a pessoa cuidada. Defende-se, portanto, que práticas como essa são necessárias e relevantes, precisam de financiamento para que possam ser levadas a outros espaços, como a rede de saúde e assistência às pessoas que recebem cuidados.
Narrative therapy practices for promoting quality of life in caregivers
Keywords: Práticas narrativas; Qualidade de vida; Cuidador; Orientação profissional; Narrative practices; Quality of life; Caregiving; Career guidance